Acute phase proteins and IP-10 in plasma for tuberculosis diagnosis - Molina-Moya, Bárbara; Villar-Hernández, Raquel; Ciobanu, Nelly; Muriel-Moreno, Beatriz; Lacoma, Alicia; Codreanu, Alexandru; Latorre, Irene; Smalchuk, Daria; Prat-Aymerich, Cristina; Crudu, Valeriu; Kontogianni, Konstantina; Cuevas, Luis E.; et al. (Frontiers in Tuberculosis, 2023)
Background. Tuberculosis (TB) is a leading cause of death from a single infectious agent, and triage tests based on biomarkers may help to improve the diagnosis. This study aims to determine whether C-reactive protein (CRP), IFN-γ-induced protein 10 (IP-10), α1-acid glycoprotein (AGP), and α1anti-trypsin (AAT) could be useful for a screening test in patients with presumptive TB disease.Methods. CRP, IP-10, AGP, and AAT were measured in plasma samples from 277 patients with presumptive TB disease in the Republic of Moldova in a prospective study.In general, the levels of all the biomarkers were higher in patients with TB than in the other groups (p<0.05). Receiver operating characteristic (ROC) curve analyses showed an area under the curve lower than 0.7 for all the biomarkers, and low correlations (Spearman r<0.6) were found between biomarkers.The levels of the tested biomarkers were different throughout the patient groups studied, but their suboptimal diagnostic performance either as individual biomarkers or in combination does not favor their use for triage testing.